Sensing Performance and Efficiency of Two Energy Transfer-Based Two-Photon Fluorescent Probes for pH - Yujin Zhang; Wei Hu (Sensors, 2018)
The design and synthesis of fluorescent probes for monitoring pH values inside living cells have attracted great attention, due to the important role pH plays in many biological processes. In this study, the optical properties of two different two-photon fluorescent probes for pH are studied. The ratiometric sensing of the probes are theoretically illustrated. Meanwhile, the recognitional mechanisms of the probes are investigated, which shows the energy transfer process when react with H+. Specially, the calculated results demonstrate that Probe1 possesses a higher energy transfer efficiency and a larger two-photon absorption cross-section than Probe2, indicating it to be a preferable pH fluorescent probe. Therefore, the influence of connection between the donor and the acceptor on the sensing performances of the probe is demonstrated. Our results help to understand the experimental observations and provide a theoretical basis to synthesize efficient two-photon fluorescent probes for monitoring pH changes.